An Entity called Sports Anemia, does it really exist or is a misnomer: A Systematic review of existing literature. - Bhatia, Tarundeep Kaur; Bhatia , Jaideep; Aryadeep (GMC Patiala Journal of Research and Medical Education, 2022)
Background: Iron is critical for optimal athletic performance because of its role in energy metabolism, oxygen transport and acid base balance. Traditionally empirical iron supplementation is done in all elite athletes because athletes involved in endurance sports have a decreased haemoglobin and haematocrit which is termed as “sports anemia.Some investigators say that the slight decrease in haematocrit after heavy physical training is brought about by increased plasma volume due to renal sodium reabsorption and water retention. They say that sports anaemia is a dilutional pseudo anaemia and is a beneficial adaptation to aerobic exercise and the ritual of routine iron supplementation in athletes is not recommended. They advocate that the decision to supplement iron should be based on serum Ferritin levels which should be monitored in conditioned athletes. Recently many other causes of anemia have been identified in sportspersons like increased iron loss, reduced iron absorption and exercise induced inflammation which needs to be treated because it is the goal of sports physicians to help every athlete achieve their maximum level of performance.The aim of our study is to review existing literature and find out whether “sports anemia” really exists or is a misnomer. Key findings : Sports anemia is not a specific clinical entity rather it should be replaced by “Anemia/Iron deficiency in sportspersons”.